Factores determinantes en la estabilidad dental luego del tratamiento ortodóntico: Scoping Review. (2022)
This Scoping Review seeks to map and describe the factors that influence dental stability after orthodontic treatment. Methodology: The electronic literature search was performed in the databases Pubmed, Web Of Science, Scopus. Screening was handled in two stages: 1. Two researchers using the Rayyan program. 2. Three researchers using the manual way, solving doubts with the advisors. Results: Studies show that recurrence is associated with different components included in 11 categories: patient engagement, patient satisfaction, retention time, dental, Spee curve, orofacial habits and musculature, growth pattern, size of dental arches, type of retainer, age and biomechanics. Conclusions: There is a need for clinical studies to conduct a systematic review with quality evidence on the factors found.